Effect of age on ground reaction force-related parameters during stair negotiation - Harms, Andrew C., author; Reiser, Raoul F., II, advisor; Tracy, Brian L., committee member; Green, David P., committee member (Colorado State University. Libraries, 2013)
Stairs are a frequently encountered obstacle in daily life. The ability to negotiate stairs without difficulty or pain is important to quality of life. Although it is a simple task for healthy adults, ascending and descending stairs can be very challenging when motor functions are diminished (e.g., in older adults, persons with physical disabilities and in persons who have experienced trauma to their lower extremities). Because many individuals with neuromuscular impairments walk and ascend/descend stairs slowly, it is important to isolate functional task from other factors such as age, muscle weakness, etc. Previous studies have presented some data on kinematics, kinetics and muscles or groups of muscles that contribute to the specific subtasks of stair negotiation. However, the complete data for Ground Reaction Force (GRF) related parameters (GRF as well as free vertical moment and center of pressure) during stair negotiation across age groups at controlled speeds has yet to be established. The purpose of this thesis was to characterize the GRF related parameters during stair negotiation in healthy young and older adults while ascending and descending stairs at a controlled speed. Ten healthy younger adults and nine healthy older adults each performed five trials of stair ascent and descent at a controlled speed (70 steps/min). A force platform was embedded in the center of the second step of a custom-built four step staircase. Subjects performed one step on the level starting surface before ascending or descending the stairs in a step-over-step manner with the right foot always contacting the force platform. Results showed that significant differences were exhibited between stair ascent and descent, with greater variability during descent. Further, significant differences existed across age groups, with older adult's also typically exhibiting greater variability of measures. Most notable were the age-group differences between loading and unloading slopes in the vertical GRF and center of pressure displacements/velocities at the beginning and end of stance, respectively. The present study is novel in the fact that it was the first to examine both differences in ascent and descent as well as age-related differences in force control at a controlled speed. Differences between groups during loading suggest reduced control of force while differences during unloading suggest a more cautious strategy in the older adults. The greater variability that existed during descent compared to ascent highlights the difficulty the ability to control eccentric contraction compared to ascent contraction, regardless of age. The age-related differences that were exhibited in the greater variability in older adults supports previous reports the lack of neuromuscular control during eccentric contractions as part of the natural aging process. Characterization of the biomechanics of stair negotiation in individuals with disabilities in clinical conditions may direct innovative rehabilitative therapies to target and strengthen impaired muscle groups so that these people can negotiate stairs with increased ease, control and independence.